Efficacy and Tolerability of Topical Polyphenon E in Multiple "Seborrheic Keratosis-Like" Lesions of the Groin in an Immunocompetent 26-Year-Old Man - Luigi Pizzini; Graziano De Luca; Massimo Milani (Karger Publishers, 2019)
Polyphenon E 10%, a green tea extract containing epigallocatechin gallate (EGCG) as the main active compound, is a topical formulation indicated for the treatment of genital warts. Polyphenon E has also shown to be very effective in the treatment of periungual and plane warts. Here, we report a dramatic clinical effect of topical treatment with polyphenon E in a subject with multiple "seborrheic keratosis-like" lesions of the genital area. An immunocompetent 26-year-old Caucasian man came to our attention in October 2018. The subject, a regular blood donor, presented several (more than 100) light brown dome-shaped papular lesions in the groin area and in the penile shaft. A clinical diagnosis of Bowenoid papulosis-like multiple condylomata of the groin was made. A 2-month imiquimod treatment did not induce any relevant improvement in terms of volume and number of lesions. A treatment with Polyphenon E, a topical green tea extract with 10% of EGCG (Veregen®), was therefore started. After 2 months of Polyphenon E treatment, a dramatic reduction of the majority of the lesions was observed. After 3 months of treatment, all the lesions disappeared with only hyperchromic residues. Histological and immunohistological findings supported seborrheic keratosis as the conclusive diagnosis. This case report suggests that topical green tea extract could be very effective in the treatment of "seborrheic keratosis-like" lesions of the inguinal area.